Phosphorus dynamics in the rhizosphere of sugarcane under phosphate sources and filter cake - Arruda, Bruna (2015)
In tropical soils, phosphorus (P) is adsorbed onto the oxide surface reducing the availability to plants. Thus, the solubility of the P sources and the particular plant characteristics which increases the absorption efficiency becomes important in the rhizosphere where roots and soil microorganisms interacts together. The objectives of this research were to evaluate sugarcane cultivars in relation to changes in the rhizosphere and the efficiency of P absorption and to evaluate the dynamics of P in the rhizosphere of sugarcane under the application of filter cake combined with mineral fertilizers. Four experiments were conducted in a greenhouse. The soil was a sandy clay loam Ferralsol from Piracicaba - SP, with low soil P, arranged in a randomized block design with four replications for each experiment. The experiment 1 was conducted in a 5x2 factorial arrangement with four sugarcane cultivars: RB92-579; RB85-5156; RB86-7515; RB86-6928 or no plants subjected to presence or absence of phosphate fertilizer (78.4 mg P kg-1) and soil adhering to the root was considered rhizosphere. The experiment 2 evaluated five doses of phosphate fertilizers: 0; 9.8; 19.6; 39.2 and 78.4 mg P kg-1 soil with the most promising cultivar for P absorption from experiment 1, and the rhizosphere was collected in five distances from the rhizoplane (mm): i) 0-2; ii) 2-4; iii) 4-6; iv) 6-8; v) 8-10. Experiment 3 was conducted in a 2x3 factorial: absence or presence of filter cake (5 g DM kg-1) with rock phosphate, soluble phosphate (78.4 mg soluble P kg-1 soil) or phosphate absence, and the rhizosphere soil was sampled 2 mm from the rhizoplane. Experiment 4 involved five filter cake rates: 0; 2.5; 5; 10 and 15 g DM kg-1 applied to the bulk soil or in the planting furrow. The cultivar RB96-6928 showed better adaptation characteristics under low availability of phosphorus, with good root development and P uptake. The rate 38.5 mg P kg-1 was the most suitable to promote optimal seedling development. The filter cake was efficient to increase P uptake and the interaction between filter cake and rock phosphate was efficient to increase production factors as the number of tillers per plant. The highest P uptake occurred when filter cake was applied to planting furrow at a rate of 10 g DM kg-1.